Exploring the Joint Association Between Agrichemical Mixtures and Pediatric Cancer - Jabeen Taiba; Cheryl Beseler; Muhammad Zahid; Shannon Bartelt‐Hunt; Alan Kolok; Eleanor Rogan (GeoHealth)
Abstract Nebraska's age‐adjusted incidence rates for childhood cancers are among the highest in the US. Previous studies indicated associations between agrichemical exposures (atrazine and nitrates) and pediatric cancer rate, assuming single pollutant exposure. We evaluated the joint association between the agricultural mixture and pediatric cancer. Agrichemical exposures at a county scale were quantified using the USGS Pesticide National Synthesis Project for frequently applied pesticides from 1992 to 2014 in 93 Nebraska counties. Outcomes were quantified using pediatric cancer diagnosed among children <20 years of age (1992–2014) from the Nebraska cancer registry. We adjusted for social vulnerability factors such as race, income, employment, and access to care. The associations between 32 agrichemicals and cancer subtypes were assessed using the Generalized Weighted Quantile Sum Regression (gWQS) model. The model was fit assuming a Poisson distribution and using the pediatric population as an offset‐term and social vulnerability factors as covariates. We observed a statistically significant positive association between the 32 agrichemicals and overall pediatric cancer and subtypes. The strength of associations was slightly stronger among brain and CNS cancers (β = 0.36, CI = 0.14, 0.57) compared to overall cancer (β = 0.30, CI = 0.16, 0.44) and leukemia (β = 0.23, CI = 0.09, 0.38). Dicamba, glyphosate, paraquat, quizalofop, triasulfuron, and tefluthrin largely contributed to the joint association. These findings may explain the joint associations of the agrichemical mixture on childhood cancer. Alternative biomarker‐based approaches to measuring human exposure are worth investigating for chemicals of concern, particularly in counties with high agrichemical and cancer rates.